EFEKTIVITAS PENGAWETAN BAMBU PETUNG DAN GEWANG MENGGUNAKAN BORON DAN CCB SECARA RENDAMAN DINGIN DAN BOUCHERIE YANG DIMODIFIKASI - Made Widiadnyana Wardiha; Rudi Setiadji Agustiningtyas; I Wayan Avend Mahawan Sumawa (Jurnal Penelitian Hasil Hutan, 2018)
Bamboo and gewang midrib are two materials developed as wood substitute in the shape form of lamina products. However, the disadvantage of bamboo and gewang is susceptible to destroying organisms. This paper analyzes the effectiveness of petung bamboo and gewang midrib treatment to improve its durability against destroying organisms. This research investigated the durability of petung bamboo and gewang midrib againts subterranean termites, dry wood termites, wood rotting fungi and dry wood post powder beetles. Treatments were conducted by applying boron and CCB (copper-chrome-boron) using cold immersion and modified Boucherie methods. Durability was tested according to Indonesian Standard SNI 01-7207-2006, while retention and penetration were calculated based on weight, volume, and solution concentrations. The results showed that boron was effective to improve the durability of petung bamboo againts subterranean termites, dry wood termites, and wood rotting fungi, while its resistance againts dry wood post powder beetles, boron and CCB were equally effective. Boron was more effective to improve durability to wood rotting fungi and dry wood post powder beetles in gewang midrib, while both preservatives were similarly effective against subterranean termites and dry wood termites. It is noticably that CCB treatment changed the wood natural color. Modified Boucherie method provides high retention but low penetration level compare to immersion method.